Juxta-apical radiolucency of lower third molars - Kata Janovics; Balázs Soós; Edina Lempel; Ágnes Bán; József Szalma (Hungarian Dental Association, 2021)
Juxta-apical radiolucency (JAR) is a radiographic finding, which appears as a well circumscribed radiolucent area lateral to the root rather than at the apex of the mandibular third molars. Some authors suggested the presence of JAR being associated with the elevated risk of inferior alveolar nerve injury during wisdom tooth removal, while other studies failed to prove any correlations. The aim of the present study was to review the international literature and to describe the concept of JAR for the Hungarian scientific literature. JAR is a common finding it is found in 33% of third molars. Based on literature data it seems that the image of the JAR is created by the superimposition of cancellous bony architecture, and JAR per se is not a sign of increased risk for inferior alveolar nerve injury. However, knowledge of JAR is important for the practicing dentists and oral surgeons both from a diagnostic and surgical point of view. Assessing the indication of wisdom teeth removal or during dental foci examination a differential diagnostic problem may arise in connection with the JAR. JAR may be an important factor when estimating the risk for inferior alveolar nerve injury since it may increase the risk on its own and even make it more difficult to assess other risk factors.